2023
DOI: 10.1093/rb/rbad052
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-small superparamagnetic iron oxide nanoparticles for intra-articular targeting of cartilage in early osteoarthritis

Abstract: Early diagnosis of osteoarthritis (OA) is critical for effective cartilage repair. However, lack of blood vessels in articular cartilage poses a barrier to contrast agent delivery and subsequent diagnostic imaging. To address this challenge, we proposed to develope ultra-small superparamagnetic iron oxide nanoparticles (SPIONs, 4 nm) that can penetrate into the matrix of articular cartilage, and further modified with the peptide ligand WYRGRL (particle size, 5.9 nm), which allows SPIONs to bind to type II coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 43 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…In addition, the conclusions of this study also provide a basis for the public health system to strengthen the monitoring of OA occurrence in hyperthyroidism patients. Cartilage injury, subchondral bone destruction, and chondrocyte hypertrophy are significant pathological features of OA 40,41 and are also the main pathological factors for the occurrence and progression of OA. Rim et al showed that the TSH receptor is highly expressed in chondrocytes 42 , but the role and mechanism of TSH in chondrocyte differentiation have not yet been revealed.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the conclusions of this study also provide a basis for the public health system to strengthen the monitoring of OA occurrence in hyperthyroidism patients. Cartilage injury, subchondral bone destruction, and chondrocyte hypertrophy are significant pathological features of OA 40,41 and are also the main pathological factors for the occurrence and progression of OA. Rim et al showed that the TSH receptor is highly expressed in chondrocytes 42 , but the role and mechanism of TSH in chondrocyte differentiation have not yet been revealed.…”
Section: Discussionmentioning
confidence: 99%
“…A liposome (LP), a special nanocarrier similar to biological membranes, has been successfully applied for the targeted delivery of antitumor drugs owing to its nonimmunogenic characteristics and high loading capacity, such as Doxil, Onivyde, and other clinical nanoformulations, demonstrating great potential for current cancer therapy. By virtue of the slow release and the enhanced permeability and retention (EPR) effect, LPs can promote the accumulation in tumor tissues of therapeutic agents, achieving reduced systemic toxicity and improved efficacy. , Cholesterol, as one of the main constituents of LPs, has a crucial role in maintaining the stability and regulating the fluidity of the lipid bilayer membrane. However, it also exists with a multitude of limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, joint replacement surgery is typically reserved for severe joint degeneration and damage and is not suitable for all patients [ 4 ]. Tissue engineering technology offers a new avenue for cartilage injury repair, particularly through the utilization of biofunctional scaffolds with suitable 3D porous structures [ 5 ]. Natural materials, despite the availability of synthetic alternatives, exhibit superior attributes, such as strong biocompatibility, heightened biofunctional activity and an environment mimicking native conditions [ 6 ].…”
Section: Introductionmentioning
confidence: 99%